Cold tolerance in Arabidopsis kamchatica. Issue 3 (1st March 2015) - Armstrong, Jessica J.; Takebayashi, Naoki; Sformo, Todd; Wolf, Diana E.
Abstract : Premise of the study: Cold tolerance is a critically important factor determining how plants will be influenced by climate change, including changes in snowcover and extreme weather events. Although a great deal is known about cold tolerance in Arabidopsis thaliana, it is not highly cold tolerant. This study examined cold tolerance and its genetic diversity in an herbaceous subarctic relative, Arabidopsis kamchatica, which generally occurs in much colder climates. Methods: Thermal analysis and electrolyte leakage were used to estimate supercooling points and lethal temperatures (LT50 ) in cold‐acclimated and nonacclimated families from three populations of A. kamchatica . Key results: Arabidopsis kamchatica was highly cold tolerant, with a mean LT50 of −10.8°C when actively growing, and −21.8°C when cold acclimated. It also was able to supercool to very low temperatures. Surprisingly, actively growing plants supercooled more than acclimated plants (−14.7 vs. −12.7°C). There was significant genetic variation for cold tolerance both within and among populations. However, both cold tolerance and genetic diversity were highest in the midlatitude population rather than in the far north, indicating that adaptations to climate change are most likely to arise in the center of the species range rather than at the edges. Conclusions: Arabidopsis kamchatica is highly cold tolerant throughout its range. It is far more freeze tolerant than A. thaliana, and supercooled to lower temperatures, suggesting that A. kamchatica provides a valuable complement to A. thaliana for cold tolerance research.